Multisectoral Action to Combat Regional and Social Inequities in Health 2017
DOI: 10.26911/theicph.2017.135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Doctor’s Personality, Job Characteristic, Payment Method, Facility, on Performance and Quality of Doctor Service

Abstract: Background: Doctors generally do not work permanently at hospitals. Doctors are expected to deliver quality medical service at the hospitals. However, hospitals often find it difficult to exercise efective managerial control over the quality of medical services. This study aimed to investigate the effect of doctor's personality, job characteristic, payment method, facility, on performance and quality of doctor service. Subjects and Method: This was an analytic observational study using cross-sectional design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Extraversion is characterized by being confident, sociable, assertive, and relationship-oriented. Extraversion positively and significantly influences services in Indonesia due to employees working confidently and striving to perform better (Hastuti et al, 2017), similar to the findings in Turkey (Köşker et al, 2019) and Taiwan (Teng et al, 2007). Extraversion has a positive but insignificant effect on customer-oriented behavior in Thailand (Mechinda & Patterson, 2011) and Seoul (Kim & Lee, 2016), as well as on service-oriented industries in Indonesia (Qaniah & Nurwianti, 2021).…”
Section: Literature Reviewsupporting
confidence: 72%
“…Extraversion is characterized by being confident, sociable, assertive, and relationship-oriented. Extraversion positively and significantly influences services in Indonesia due to employees working confidently and striving to perform better (Hastuti et al, 2017), similar to the findings in Turkey (Köşker et al, 2019) and Taiwan (Teng et al, 2007). Extraversion has a positive but insignificant effect on customer-oriented behavior in Thailand (Mechinda & Patterson, 2011) and Seoul (Kim & Lee, 2016), as well as on service-oriented industries in Indonesia (Qaniah & Nurwianti, 2021).…”
Section: Literature Reviewsupporting
confidence: 72%
“…Additional research evidence confirms that in a task that requires cooperative communication, conscientiousness and agreeableness have a significant impact on job performance [ 31 ]. In Indonesia, it was shown that the extrovert personality among physicians results in optimal work performance [ 32 ]. Another study showed that personality moderates the coping styles to influence the anxiety symptoms among Chinese physicians [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self efikasi ini sangat berpengaruh perannya dalam usaha yang dilakukan, seberapa kuat usahanya dalam memprediksi keberhasilan yang akan dicapai. Self Efficacy merupakan penilaian seseorang terhadap dirinya sendiri atau tingkat keyakinan mengenahi seberapa besar kemmpuan dalam mengerjakan suatu tugas tertentu untuk mencapai hasil tertentu (Hastuti et al, 2017).…”
Section: Grafik 4 Harga Diri (Self Esteem)unclassified